Grain issue in relations between Ukraine and the EU - Donaj, Łukasz; Us, Ivan; Radziyevska, Svitlana (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2023)
The paper focuses on grain issue in relations between Ukraine and the EU. The objective of the study is to reveal the reasons for the complication of relations between Ukraine and the countries of Central and Eastern Europe in the spring of 2023. To achieve the objective, the authors: 1) analyze which EU countries themselves have introduced separate restrictive measures against Ukraine; 2) reveal the dynamics of the physical volumes of grain exports from Ukraine; 3) consider the legal aspect of the application of restrictive measures; 4) determine the consequences of measures, and 5) calculate Ukraine’s potential losses. It is underlined that the political step of the EU aimed at supporting the economy of Ukraine in the conditions of the war created additional pressure on the farmers of Central and Eastern European countries, because the warehouse system of these countries was not ready for a significant increase in supplies from Ukraine. The steps taken by the governments of some Central and Eastern European countries ran counter to their obligations as EU members and violated the Association Agreement between Ukraine and the EU. In addition, these steps created the preconditions for an institutional crisis in the EU. It is concluded that avoiding similar problems in the future requires a solution in the triangle Ukraine–European Commission–individual EU members. Artykuł koncentruje się na problematyce zbożowej w stosunkach między Ukrainą a UE. Celem opracowania jest wskazanie przyczyn komplikacji stosunków między Ukrainą a państwami Europy Środkowo-Wschodniej wiosną 2023 roku. W tym celu autorzy: 1) skoncentrowali swoją uwagę na państwach UE, które arbitralnie wprowadziły odrębne środki ograniczające eksport ukraińskiego zboża; 2) przeanalizowali dynamikę fizycznych wielkości eksportu zboża z Ukrainy; 3) rozważyli prawne aspekty zastosowania środków ograniczających; 4) określili konsekwencje działań oraz 5) obliczyli potencjalne straty Ukrainy. W efekcie, ustalono że polityczny krok UE mający na celu wsparcie gospodarki Ukrainy w warunkach wojny wywołał dodatkową presję na rolnikach państw Europy Środkowo-Wschodniej. Spowodowane to było faktem niedostatecznego przygotowania systemów magazynowania tych państw. Podkreślić przy tym należy, że działania podjęte przez rządy niektórych państw Europy Środkowej i Wschodniej były sprzeczne z ich zobowiązaniami jako członków UE i naruszyły układ stowarzyszeniowy między Ukrainą a UE. Ponadto kroki te stworzyły warunki wstępne do wystąpienia kryzysu instytucjonalnego w UE. Uniknięcie podobnych problemów w przyszłości wymaga rozwiązań wypracowywanych w trójkącie Ukraina–Komisja Europejska–poszczególni członkowie UE.
Eksport zboża a stosunki między Ukrainą a UE
Keywords: grain exports from Ukraine; the countries of Central and Eastern Europe; the EU institutional crisis; Ukraine’s potential losses; eksport zboża z Ukrainy; państwa Europy Środkowo-Wschodniej; kryzys instytucjonalny UE; potencjalne straty Ukrainy